A ceramsite fracturing proppant prepared by using power plant ash and preparation method thereof

By using materials such as power plant ash slag and fly ash to prepare ceramic fracturing proppants, combined with sintering aids and improvers, the problems of high density and high production cost of ceramic proppants are solved, and low density, high strength and environmental protection are achieved The ceramic fracturing proppant meets the needs of oil extraction.

CN118308085BActive Publication Date: 2024-12-20XINMI WANLI IND DEV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410423242.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-09
Publication Date
2024-12-20
Estimated Expiration
2044-04-09

AI Technical Summary

Technical Problem

The existing ceramic proppants have high density, high production costs and are prone to settlement, which is difficult to meet the requirements of low density and high strength, and the treatment of industrial waste is not environmentally friendly.

Method used

Power plant ash slag and fly ash are used as the main raw materials, and are equipped with soft clay, manganese powder, dolomite and magnesium sand. Through the combination of sintering additives and improved agents, the density of proppant is reduced, and the anti-brokening ability and density are improved. The chemical composition of ash slag and fly ash forms a low-cost, high-performance ceramic fracturing proppant.

Benefits of technology

The low-density and high-strength characteristics of ceramic fracturing proppants are achieved, which reduces production costs, and effectively utilizes industrial waste and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004783119150000121
    Figure BDA0004783119150000121
  • Figure BDA0004783119150000131
    Figure BDA0004783119150000131
Patent Text Reader

Abstract

The present application discloses a ceramsite fracturing proppant prepared by using power plant ash and a preparation method thereof, and relates to the technical field of petroleum fracturing proppant. The ceramsite fracturing proppant prepared by using power plant ash comprises the following raw materials in parts by weight: 5 to 35 parts by weight of ash, 5 to 15 parts by weight of fly ash, 1 to 5 parts by weight of soft clay, 30 to 55 parts by weight of bauxite, 1 to 5 parts by weight of manganese powder, 1 to 3 parts by weight of dolomite, and 1 to 3 parts by weight of magnesia. The ceramsite fracturing proppant prepared by the present application has lower bulk density, apparent density and stronger anti-crushing ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of petroleum fracturing proppants, and in particular to a ceramsite fracturing proppant prepared by utilizing power plant ash and a preparation method thereof. Background Art

[0002] With the development of economy, the output of ash is gradually increasing. If it is not handled properly, it will seriously pollute the environment and cause serious harm to people's lives, the growth of animals and plants, etc. Ash refers to the final product formed after the minerals in the coal are burned in the furnace under the high temperature and undergo certain physical and chemical changes. Ash is a heavier substance, which is usually deposited at the bottom of the boiler, so it is also called "boiler slag" or "bottom slag". Fly ash is a lighter substance that will float faster in the flue gas, so it is usually called "smoke ash". Most of the fly ash is a highly dispersed aggregate of spheres or microspheres. Compared with ash, it has weaker bonding force, poorer compressive resistance and wear resistance. In view of the chemical composition and excellent mechanical, chemical and other properties of ash, the preparation of low-cost, high-performance fracturing proppants with ash as the main raw material has both environmental and economic benefits.

[0003] Fracturing proppant is a key material in the fracturing and production-increasing technology in oil extraction. It creates cracks in the rock strata around the wellbore at a pressure that exceeds the fracture strength of the formation, forming a channel with high-level flow capacity, and keeps the cracks formed after fracturing open, allowing oil and gas products to pass smoothly, thereby increasing oil extraction output.

[0004] A Chinese invention patent application with application publication number CN101560382A discloses a high-strength ceramsite proppant, characterized in that it is prepared from 100 parts of bauxite powder, 2 to 20 parts of manganese ore powder, 0.5 to 3 parts of titanium concentrate powder, 3 to 10 parts of bentonite and 1 to 5 parts of magnesium oxide, calculated by weight.

[0005] The Al2O3 content in the bauxite powder used in the high-strength ceramsite proppant is 85% or more. Although the ceramsite proppant obtained has high strength and low crushing resistance, its bulk density, apparent density and production cost are also high. The proppant has a high density and a fast sedimentation rate, and is very easy to settle near the wellbore, which places extremely high requirements on the performance of the fracturing fluid and pumping conditions. Therefore, under the condition of ensuring the good performance of the proppant, the proppant is required to have the characteristics of low density and high strength. Summary of the invention

[0006] In order to prepare a proppant with low density and strong crushing resistance, the present application provides a ceramsite fracturing proppant prepared by using power plant ash and a preparation method thereof.

[0007] The present application provides a ceramsite fracturing proppant prepared by using power plant ash, which adopts the following technical solution:

[0008] The invention discloses a ceramsite fracturing proppant prepared by using power plant ash. The ceramsite fracturing proppant is made of the following raw materials in parts by weight: 5 to 35 parts by weight of ash, 5 to 15 parts by weight of fly ash, 1 to 5 parts by weight of soft clay, 30 to 55 parts by weight of bauxite, 1 to 5 parts by weight of manganese powder, 1 to 3 parts by weight of dolomite and 1 to 3 parts by weight of magnesia.

[0009] In this technical solution, the use of ash and fly ash with high silicon dioxide content can not only improve the utilization rate of industrial waste, but also reduce the pollution of industrial waste to the environment, which has a certain environmental protection effect. Ash and fly ash, as industrial waste, are mainly composed of chemical components such as Al2O3, SiO2, Fe2O3 and TiO2, among which SiO2 has the highest content, accounting for 45% to 60%, followed by Al2O3, accounting for 20% to 30%. First, the ash and fly ash are light and have a small loss on ignition, which can effectively reduce the density of the proppant; secondly, the main components of ash and fly ash are similar to the chemical composition of mullite. The use of ash, fly ash and bauxite to compound the proppant is helpful to save resources and protect the environment. The ground ash has good compressive strength, wear resistance and bonding ability, and is similar to the composition of bauxite, so it is easier to bond. The particle structure of fly ash has good filling properties, and doping a certain amount of fly ash can improve the compactness of the proppant.

[0010] The addition of soft clay can enhance the bonding force between the components of the proppant, thereby improving the stability and anti-crushing ability of the proppant. Manganese powder can make bauxite reach higher strength at a lower sintering temperature. This is mainly because the ionic radius of manganese ions (fourth order) is close to the ionic radius of aluminum ions (third order) in the corundum phase. A solid solution reaction occurs at high temperature, so that manganese ions replace part of the aluminum ions to form a solid solution. At the same time, manganese ions and aluminum ions have different chemical valences, which causes the lattice distortion of aluminum oxide and activates the lattice, accelerates the ion diffusion rate, effectively reduces the sample sintering temperature, and improves the fluidity of the micro-liquid phase, making the inside of the proppant more dense. In addition, manganese dioxide has a strong nucleation ability, which can effectively improve the crystallization ability of the sample during the cooling process, reduce the generation of glass phase, and thus improve the strength of the proppant.

[0011] The further addition of dolomite and magnesia increases the content of CaO and MgO in the sintering material. Therefore, in addition to the in-situ formation of a good calcium ferrite (CaO·FeO) liquid phase system, a new calcium forsterite (CaO·MgO·SiO2) liquid phase system is also generated, which increases the amount of liquid phase and changes its properties. Specifically, the liquid phase changes from the original dispersed phase to a continuous phase; MgO has good slag-forming properties and is easy to form calcium forsterite, which reduces the amount of free CaO and inhibits the formation of dicalcium silicate (2CaO·SiO2); (3) If dicalcium silicate is generated, it is wrapped by the continuous calcium ferrite and calcium forsterite liquid phase system, and the crystal transformation is restricted. In addition, due to the formation of the calcium forsterite liquid phase system, some high melting point minerals will be derived, which can serve as the crystallization core during cooling, thereby reducing the glass phase. Therefore, dolomite and magnesia not only greatly promote the speed of solid phase reaction, but also accelerate the filling of voids, promote the densification of samples, and also improve the compressive strength and crushing resistance of proppants.

[0012] Preferably, the ash is placed in an electric constant temperature drying oven at 100-120° C. and dried for 22 to 26 hours before use.

[0013] Preferably, the soft clay and bauxite are uncalcined raw materials.

[0014] Preferably, the bauxite is high-iron bauxite, and the content of Fe2O3 in the high-iron bauxite is 22% to 25%.

[0015] Under high temperature conditions, high iron bauxite undergoes primary mullite formation and secondary mullite formation to synthesize mullite embryos. Then, during the crystallization, development, and growth of the embryos, Fe 3+ / Ti 4+ Replace and occupy the tetrahedral or octahedral position of aluminum ions in the mullite lattice to form Fe 3+ / Ti 4+ To maintain the charge balance, some of the silicon ions in the tetrahedron diffuse out of the lattice and enter the surrounding silicate phase or form crystalline phases such as quartz; at the same time, negatively charged vacancies are left in the original lattice position, further forming Fe 3+ 、Al 3+ 、Ti 4+ Plasma diffusion and migration to the mullite lattice provide channels and accelerate the crystallization and growth of mullite. The mullite formed is composed of [AlO4] and [SiO4] tetrahedrons arranged disorderly along the c-axis to form double chains, and [AlO6] octahedrons connect the double chains to form a crystal structure with needles and columns. In the mullite mineral structure, the [AlO6] octahedral chain can play a supporting role in stabilizing the skeleton. This composition and structural characteristics make mullite wear-resistant, anti-oxidation, low thermal conductivity, low high-temperature creep, low thermal expansion coefficient and good thermal shock resistance.

[0016] Preferably, the bauxite includes high-grade bauxite and low-grade bauxite, and the mass ratio of the high-grade bauxite to the low-grade bauxite is 2-3:4-5.

[0017] In the Al2O3-SiO2 system, the only stable compound is mullite (3Al2O3·2SiO2), and the theoretical composition of mullite has a w(Al2O3) / w(SiO2) ratio of 2.55. By optimizing the ratio of high-grade bauxite to low-grade bauxite, when the content of Al2O3 and SiO2 in bauxite is close to the theoretical combination of mullite, it is easy to form a material with mullite as the main crystal phase after sintering. This material has good high-temperature mechanical properties and thermal shock resistance, thereby improving the thermal stability and anti-crushing ability of the proppant.

[0018] Preferably, the raw material further comprises 2 to 4 parts by weight of a modifier, wherein the modifier is a silicate, and the silicate is at least one of zinc silicate and barium silicate.

[0019] Zinc silicate can increase the sintering temperature and sintering density of raw materials, improve the mechanical properties and chemical stability of raw materials; zinc silicate can also adjust the thermal expansion coefficient of raw materials, reduce thermal stress at high temperatures, and reduce crystal deformation. During high sintering, barium silicate can improve the density of raw materials and reduce the generation of pores, thereby improving the density and strength of proppants; barium silicate can also stabilize the structure and shape of proppants and reduce the risk of deformation and cracking.

[0020] Preferably, the raw material further comprises 2 to 4 parts by weight of a sintering aid, and the sintering aid is at least one of non-metallic borides, chromium trioxide, and zirconium dioxide.

[0021] By adopting the above technical solution, the sintering aid can form a solid solution with the sintering body, change the lattice structure, promote the bonding between particles, and thus accelerate the sintering process. In the liquid phase, the diffusion mass transfer resistance is small and the flow mass transfer rate is fast, which helps to reduce the sintering temperature and increase the density of the proppant.

[0022] Preferably, the non-metallic boride is any one of boric acid and boron nitride.

[0023] By adopting the above technical solution, the boric acid molecule contains three hydroxyl groups, which can form a complex with metal oxides or hydroxides and participate in redox reactions, thereby changing the melting point and viscosity. Boric acid sintering aids increase the fluidity of the molten material while lowering the melting point, which helps remove impurities. Adding boron nitride can significantly improve the thermal stability of Al2O3 and SiO2 during sintering, reduce thermal expansion and deformation problems, and at the same time improve the ability of the proppant to resist chemical erosion and reduce corrosion.

[0024] Preferably, the boron nitride is hexagonal boron nitride.

[0025] Preferably, the raw material further comprises 1 to 3 parts by weight of coal tar.

[0026] By adopting the above technical solution, coal tar pitch contains a large amount of hydrocarbons, which will decompose and burn at high temperatures, and the generated gas can promote the sintering and densification of various components in the material. This helps to improve the density, hardness and strength of the material, while reducing the porosity and water absorption of the proppant, thereby improving the compressive and crushing resistance of the proppant.

[0027] Preferably, the raw material further comprises 1 to 3 parts by weight of an auxiliary agent, and the auxiliary agent is at least one of magnesium chloride and aluminum dihydrogen phosphate.

[0028] Aluminum dihydrogen phosphate can improve sintering strength and inhibit oxidation reactions, and improve the high thermal shock strength and wear resistance of the proppant. At high temperatures, aluminum dihydrogen phosphate can react with magnesium oxide to form a three-dimensional network structure through ionic bonds and covalent bonds, which has a high bonding cohesion. Magnesium chloride allows sintering to be carried out at a lower temperature, which helps save energy and reduce production costs; and it can form a liquid mineral phase at high temperatures, promote the mutual bonding between powder particles, and improve the density and strength of the material. When the proppant is used, the residual magnesium oxide and magnesium chloride in the proppant can also act as a binder when they meet water, increasing the cohesion inside the proppant, thereby improving the proppant's ability to resist crushing.

[0029] The present application also provides a method for preparing ceramsite fracturing proppant using power plant ash, comprising the following steps: S1: weighing and crushing each raw material, mixing and grinding, sieving, spray granulating, and drying to obtain a semi-finished product;

[0030] S2: Sintering the semi-finished product in stages, heating from 100-120°C to 750-850°C for 1-2h, heating from 750-850°C to 1120-1150°C for 1.5-2.5h, then keeping the temperature at 1120-1150°C for 20-60min, cooling and screening to obtain ceramsite fracturing proppant.

[0031] In summary, the present application includes at least one of the following beneficial technical effects:

[0032] 1. The present invention uses bauxite and ash as main raw materials, and adds appropriate amounts of fly ash, soft clay, manganese powder, dolomite and magnesia. In addition to the main components of the ash being similar to the mullite component, the ash can be easily combined with bauxite under the action of other additives. The ash can also reduce the thermal expansion coefficient during sintering of the raw materials, reduce the density of the proppant, and improve the anti-crushing ability and temperature resistance of the proppant; in addition, compared with fly ash, the ash has more lasting compressive resistance and stronger wear resistance, and the prepared fracturing proppant has more lasting compressive strength and anti-crushing ability.

[0033] 2. The present invention uses bauxite and ash as main raw materials, and adds appropriate amounts of fly ash, soft clay, manganese powder, dolomite and magnesia. With the help of sintering aids and improvers, the density and stability of the proppant are improved, and the anti-breakage ability of the proppant is further improved. In addition, by rationally utilizing ash and fly ash, the production cost can be reduced while reducing pollution to the environment. DETAILED DESCRIPTION

[0034] Preferably, the ash is purchased from Zhengzhou Yuzhong Energy Co., Ltd. The main chemical components of the ash are 22.79% Al2O3, 53.39% SiO2, 6.71% Fe2O3 and 1.23% TiO2.

[0035] In the following embodiments:

[0036] The main chemical components of fly ash are 28.21% Al2O3, 47.02% SiO2, 7.50% Fe2O3 and 1.22% TiO2.

[0037] The main chemical components of soft clay are 33.11% Al2O3, 43.35% SiO2, 4.65% Fe2O3 and 2.28% TiO2.

[0038] The content of MnO2 in manganese powder is 50.03%.

[0039] The main chemical components of dolomite are 29.67% CaO, 19.37% MgO, and 45.47% LOI.

[0040] The MgO content in magnesia is 90.46%.

[0041] The main chemical components of high-iron bauxite are 43.64% Al2O3, 15.96% SiO2, 24.08% Fe2O3 and 2.17% TiO2.

[0042] The main chemical components of high-grade bauxite are 70.39% Al2O3, 14.32% SiO2, 6.71% Fe2O3 and 3.15% TiO2.

[0043] The main chemical components of low-grade bauxite are 48.17% Al2O3, 28.11% SiO2, 4.92% Fe2O3 and 4.64% TiO2.

[0044] The present application is further described in detail below with reference to the embodiments.

[0045] Example 1

[0046] This embodiment provides a method for preparing ceramsite fracturing proppant using power plant ash, comprising the following steps:

[0047] S1: After slag, fly ash, soft clay, bauxite, manganese powder, dolomite and magnesia are pulverized respectively, 5 kg slag, 5 kg fly ash, 1 kg soft clay, 30 kg bauxite, 1 kg manganese powder, 1 kg dolomite and 1 kg magnesia are evenly mixed to obtain a mixed material; the mixed material is finely ground by a vibration mill and passed through a 400-mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45 to 0.9 mm, and the moisture content of the spherical particles is 11.5% to 17.5%; then the spherical particles are placed in a constant temperature box and dried at 110° C. for 2 hours to obtain a semi-finished product;

[0048] S2: The semi-finished product is transported to a rotary kiln for staged sintering, and the temperature is raised from 120°C to 750°C for 1 hour, and from 750°C to 1120°C for 1.5 hours. Then, it is kept at 1120°C for 60 minutes, and is removed from the kiln when it is cooled to about 200°C. It is then naturally cooled to room temperature, first passed through a 20-mesh sieve, and the undersize is taken, and then passed through a 40-mesh sieve, and the oversize is taken to obtain the expanded clay fracturing proppant.

[0049] The obtained ceramsite fracturing proppant is spherical particles with a particle size distribution of 0.425mm to 0.85mm; and the bauxite is high-iron bauxite.

[0050] When the mixed material is ground by a vibration mill, the mixed material can be ground repeatedly until the mixed material completely passes through a 400-mesh sieve.

[0051] Before the ash is crushed, it is placed in an electric constant temperature drying oven at 110°C and dried for 24 hours.

[0052] Example 2

[0053] This embodiment provides a method for preparing ceramsite fracturing proppant using power plant ash, comprising the following steps:

[0054] S1: After slag, fly ash, soft clay, bauxite, manganese powder, dolomite and magnesia are pulverized respectively, 10 kg slag, 5 kg fly ash, 2 kg soft clay, 40 kg bauxite, 3 kg manganese powder, 2 kg dolomite and 2 kg magnesia are evenly mixed to obtain a mixed material; the mixed material is ground into powder by a vibration mill and passed through a 400-mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45 to 0.9 mm, and the moisture content of the spherical particles is 11.5% to 17.5%; the spherical particles are then placed in a constant temperature box and dried at 110° C. for 2 hours to obtain a semi-finished product;

[0055] S2: The semi-finished product is transported to a rotary kiln for staged sintering, and the temperature is raised from 100°C to 850°C for 1.5 hours, and from 850°C to 1135°C for 2 hours. Then, it is kept at 1135°C for 50 minutes, and is removed from the kiln when it is cooled to about 200°C. It is then naturally cooled to room temperature, first passed through a 20-mesh sieve, and the undersize is taken, and then passed through a 40-mesh sieve, and the oversize is taken to obtain the expanded clay fracturing proppant.

[0056] The obtained ceramsite fracturing proppant is spherical particles with a particle size distribution of 0.425mm to 0.85mm; and the bauxite is high-iron bauxite.

[0057] When the mixed material is ground by a vibration mill, the mixed material can be ground repeatedly until the mixed material completely passes through a 400-mesh sieve.

[0058] Before the ash is crushed, it is placed in an electric constant temperature drying oven at 120°C and dried for 22 hours.

[0059] Example 3

[0060] This embodiment provides a method for preparing ceramsite fracturing proppant using power plant ash, comprising the following steps:

[0061] S1: After slag, fly ash, soft clay, bauxite, manganese powder, dolomite and magnesia are pulverized respectively, 20 kg slag, 10 kg fly ash, 3 kg soft clay, 45 kg bauxite, 4 kg manganese powder, 3 kg dolomite and 3 kg magnesia are evenly mixed to obtain a mixed material; the mixed material is ground into powder by a vibration mill and passed through a 400-mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45 to 0.9 mm, and the moisture content of the spherical particles is 11.5% to 17.5%; the spherical particles are then placed in a constant temperature box and dried at 110° C. for 2 hours to obtain a semi-finished product;

[0062] S2: The semi-finished product is transported to a rotary kiln for staged sintering, and the temperature is raised from 110°C to 800°C for 2 hours, and from 800°C to 1120°C for 2.5 hours. Then, it is kept at 1120°C for 40 minutes, and taken out of the kiln when it is cooled to about 200°C. It is then naturally cooled to room temperature, first passed through a 20-mesh sieve, and the undersize is taken, and then passed through a 40-mesh sieve, and the oversize is taken to obtain the expanded clay fracturing proppant.

[0063] The obtained ceramsite fracturing proppant is spherical particles with a particle size distribution of 0.425mm to 0.85mm; and the bauxite is high-iron bauxite.

[0064] When the mixed material is ground by a vibration mill, the mixed material can be ground repeatedly until the mixed material completely passes through a 400-mesh sieve.

[0065] Before the ash is crushed, it is placed in an electric constant temperature drying oven at 100°C and dried for 26 hours.

[0066] Example 4

[0067] This embodiment provides a method for preparing ceramsite fracturing proppant using power plant ash, comprising the following steps:

[0068] S1: After slag, fly ash, soft clay, bauxite, manganese powder, dolomite and magnesia are pulverized respectively, 35 kg slag, 15 kg fly ash, 5 kg soft clay, 55 kg bauxite, 5 kg manganese powder, 3 kg dolomite and 3 kg magnesia are evenly mixed to obtain a mixed material; the mixed material is ground into powder by a vibration mill and passed through a 400-mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45 to 0.9 mm, and the moisture content of the spherical particles is 11.5% to 17.5%; the spherical particles are then placed in a constant temperature box and dried at 110° C. for 2 hours to obtain a semi-finished product;

[0069] S2: The semi-finished product is transported to a rotary kiln for staged sintering, and the temperature is raised from 110°C to 800°C for 1.5 hours, and from 800°C to 1150°C for 2.5 hours. Then, it is kept at 1150°C for 20 minutes, and taken out of the kiln when it is cooled to about 200°C. It is then naturally cooled to room temperature, first passed through a 20-mesh sieve, and the undersize is taken, and then passed through a 40-mesh sieve, and the oversize is taken to obtain the expanded clay fracturing proppant.

[0070] The obtained ceramsite fracturing proppant is spherical particles with a particle size distribution of 0.425mm to 0.85mm; and the bauxite is high-iron bauxite.

[0071] When the mixed material is ground by a vibration mill, the mixed material can be ground repeatedly until the mixed material completely passes through a 400-mesh sieve.

[0072] Before the ash is crushed, it is placed in an electric constant temperature drying oven at 110°C and dried for 24 hours.

[0073] Example 5

[0074] This embodiment provides a method for preparing ceramsite fracturing proppant using power plant ash, comprising the following steps:

[0075] S1: After slag, fly ash, soft clay, bauxite, manganese powder, dolomite, magnesia and zinc silicate are pulverized respectively, 25 kg slag, 10 kg fly ash, 4 kg soft clay, 55 kg bauxite, 4 kg manganese powder, 3 kg dolomite, 3 kg magnesia and 2 kg zinc silicate are evenly mixed to obtain a mixed material; the mixed material is ground into powder by a vibration mill and passed through a 400-mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45-0.9 mm, and the moisture content of the spherical particles is 11.5%-17.5%; the spherical particles are then placed in a constant temperature box and dried at 110° C. for 2 hours to obtain a semi-finished product;

[0076] S2: The semi-finished product is transported to a rotary kiln for staged sintering, and the temperature is raised from 110°C to 800°C for 1.5 hours, and from 800°C to 1120°C for 2 hours. Then, it is kept at 1120°C for 40 minutes, and taken out of the kiln when it is cooled to about 200°C. It is then naturally cooled to room temperature, first passed through a 20-mesh sieve, and the undersize is taken, and then passed through a 40-mesh sieve, and the oversize is taken to obtain the expanded clay fracturing proppant.

[0077] The obtained ceramsite fracturing proppant is spherical particles with a particle size distribution of 0.425mm to 0.85mm; and the bauxite is high-iron bauxite.

[0078] When the mixed material is ground by a vibration mill, the mixed material can be ground repeatedly until the mixed material completely passes through a 400-mesh sieve.

[0079] Before the ash is crushed, it is placed in an electric constant temperature drying oven at 110°C and dried for 24 hours.

[0080] Example 6

[0081] The difference between this embodiment and embodiment 5 is that:

[0082] S1: After slag, fly ash, soft clay, bauxite, manganese powder, dolomite, magnesia, zinc silicate and barium silicate are pulverized respectively, 25 kg slag, 10 kg fly ash, 4 kg soft clay, 55 kg bauxite, 4 kg manganese powder, 3 kg dolomite, 3 kg magnesia, 2 kg zinc silicate and 2 kg barium silicate are evenly mixed to obtain a mixed material; the mixed material is finely ground by a vibration mill and passed through a 400-mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45-0.9 mm, and the moisture content of the spherical particles is 11.5%-17.5%; the spherical particles are then placed in a constant temperature box and dried at 110° C. for 2 hours to obtain a semi-finished product;

[0083] The rest is the same as Example 5.

[0084] Example 7

[0085] The difference between this embodiment and embodiment 6 is that:

[0086] S1: After slag, fly ash, soft clay, bauxite, manganese powder, dolomite, magnesia, zinc silicate, barium silicate and boric acid are pulverized respectively, 25 kg slag, 10 kg fly ash, 4 kg soft clay, 55 kg bauxite, 4 kg manganese powder, 3 kg dolomite, 3 kg magnesia, 2 kg zinc silicate, 2 kg barium silicate and 2 kg boric acid are evenly mixed to obtain a mixed material; the mixed material is finely ground by a vibration mill and passed through a 400 mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45-0.9 mm, and the moisture content of the spherical particles is 11.5%-17.5%; the spherical particles are then placed in a constant temperature box and dried at 110° C. for 2 hours to obtain a semi-finished product;

[0087] Among them, boric acid is white powder.

[0088] The rest is the same as Example 6.

[0089] Example 8

[0090] The difference between this embodiment and embodiment 7 is that:

[0091] S1: After slag, fly ash, soft clay, bauxite, manganese powder, dolomite, magnesia, zinc silicate, barium silicate, boric acid and hexagonal boron nitride are pulverized respectively, 25 kg slag, 10 kg fly ash, 4 kg soft clay, 55 kg bauxite, 4 kg manganese powder, 3 kg dolomite, 3 kg magnesia, 2 kg zinc silicate, 2 kg barium silicate, 2 kg boric acid and 2 kg hexagonal boron nitride are mixed evenly to obtain a mixed material; the mixed material is ground into powder by a vibration mill and passed through a 400 mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45-0.9 mm, and the moisture content of the spherical particles is 11.5%-17.5%; the spherical particles are then placed in a constant temperature box and dried at 110° C. for 2 hours to obtain a semi-finished product;

[0092] The rest is the same as Example 7.

[0093] Example 9

[0094] The difference between this embodiment and embodiment 8 is that:

[0095] S1: After slag, fly ash, soft clay, bauxite, manganese powder, dolomite, magnesia, zinc silicate, barium silicate, chromium trioxide, zirconium dioxide, hexagonal boron nitride and coal tar pitch were crushed, 25kg slag, 10kg fly ash, 4kg soft clay, 55kg bauxite, 4kg manganese powder, 3kg dolomite, 3kg magnesia, 2kg zinc silicate, 2kg barium silicate, 1kg chromium trioxide, 1kg zirconium dioxide, 2kg hexagonal boron nitride were crushed. Boron nitride and 1 kg of coal tar pitch are uniformly mixed to obtain a mixed material; the mixed material is ground into powder using a vibration mill and passed through a 400-mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45 to 0.9 mm, and the moisture content of the spherical particles is 11.5% to 17.5%; then the spherical particles are placed in a constant temperature box and dried for 2 hours at 110° C. to obtain a semi-finished product;

[0096] Among them, coal tar pitch is solid.

[0097] The rest is the same as Example 8.

[0098] Example 10

[0099] The difference between this embodiment and embodiment 9 is that:

[0100] S1: After slag, fly ash, soft clay, bauxite, manganese powder, dolomite, magnesia, zinc silicate, barium silicate, chromium trioxide, zirconium dioxide, hexagonal boron nitride and coal tar pitch were crushed, 25kg slag, 10kg fly ash, 4kg soft clay, 55kg bauxite, 4kg manganese powder, 3kg dolomite, 3kg magnesia, 2kg zinc silicate, 2kg barium silicate, 1kg chromium trioxide, 1kg zirconium dioxide, 2kg hexagonal boron nitride were crushed. Boron nitride and 3kg of coal tar pitch are uniformly mixed to obtain a mixed material; the mixed material is ground into powder using a vibration mill and passed through a 400-mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45 to 0.9 mm, and the moisture content of the spherical particles is 11.5% to 17.5%; then the spherical particles are placed in a constant temperature box and dried for 2 hours at 110°C to obtain a semi-finished product;

[0101] Among them, coal tar pitch is solid.

[0102] The rest is the same as Example 9.

[0103] Embodiment 11

[0104] The difference between this embodiment and embodiment 10 is that:

[0105] S1: After ash, fly ash, soft clay, bauxite, manganese powder, dolomite, magnesia, zinc silicate, barium silicate, zirconium dioxide, hexagonal boron nitride, coal tar and magnesium chloride are crushed, 25kg ash, 10kg fly ash, 4kg soft clay, 55kg bauxite, 4kg manganese powder, 3kg dolomite, 3kg magnesia, 2kg zinc silicate, 2kg barium silicate, 1kg zirconium dioxide, 3kg hexagonal boron nitride, 3kg coal tar and magnesium chloride are crushed. Green and 1kg of magnesium chloride are uniformly mixed to obtain a mixed material; the mixed material is ground into powder using a vibration mill and passed through a 400-mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45-0.9mm, and the moisture content of the spherical particles is 11.5%-17.5%; then the spherical particles are placed in a constant temperature box and dried for 2 hours at 110°C to obtain a semi-finished product;

[0106] Among them, coal tar pitch is solid.

[0107] The rest is the same as Example 10.

[0108] Example 12

[0109] The difference between this embodiment and embodiment 11 is that:

[0110] S1: After ash, fly ash, soft clay, bauxite, manganese powder, dolomite, magnesia, zinc silicate, barium silicate, hexagonal boron nitride, coal tar, magnesium chloride and aluminum dihydrogen phosphate were crushed, 25kg ash, 10kg fly ash, 4kg soft clay, 55kg bauxite, 4kg manganese powder, 3kg dolomite, 3kg magnesia, 2kg zinc silicate, 2kg barium silicate, 4kg hexagonal boron nitride, 3kg coal tar, 1kg magnesium chloride were crushed. , 2kg of aluminum dihydrogen phosphate and mixed evenly to obtain a mixed material; grind the mixed material with a vibration mill, pass it through a 400-mesh sieve, and obtain a fine powder of the mixed material; add the fine powder of the mixed material to a disc granulator for granulation in multiple times, and apply atomized water vapor during granulation to prepare spherical particles with a particle size of 0.45-0.9mm, and the moisture content of the spherical particles is 11.5%-17.5%; then place the spherical particles in a constant temperature box, dry them at 110°C for 2h, and obtain a semi-finished product;

[0111] Among them, coal tar pitch is solid.

[0112] The main chemical components of high-iron bauxite are 45.21% Al2O3, 15.75% SiO2, 22.25% Fe2O3 and 2.23% TiO2.

[0113] The rest is the same as Example 11.

[0114] Example 13

[0115] The difference between this embodiment and embodiment 12 is that the bauxite is compounded by high-grade bauxite and low-grade bauxite in a mass ratio of 1:2.

[0116] The rest is the same as Example 12.

[0117] Embodiment 14

[0118] The difference between this embodiment and embodiment 13 is that the bauxite is compounded by high-grade bauxite and low-grade bauxite in a mass ratio of 3:5.

[0119] The rest is the same as Example 13.

[0120] Comparative Example 1

[0121] The difference between this comparative example and Example 1 is:

[0122] S1: After fly ash, soft clay, bauxite, manganese powder, dolomite and magnesia are pulverized respectively, 10 kg fly ash, 1 kg soft clay, 30 kg bauxite, 1 kg manganese powder, 1 kg dolomite and 1 kg magnesia are evenly mixed to obtain a mixed material; the mixed material is ground into powder by a vibration mill and passed through a 400-mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45 to 0.9 mm, and the moisture content of the spherical particles is 11.5% to 17.5%; the spherical particles are then placed in a constant temperature box and dried at 110° C. for 2 hours to obtain a semi-finished product;

[0123] The rest is the same as in Example 1.

[0124] Comparative Example 2

[0125] The difference between this comparative example and Example 1 is:

[0126] S1: After slag, fly ash, soft clay, bauxite, manganese powder and dolomite are pulverized respectively, 5 kg slag, 5 kg fly ash, 1 kg soft clay, 30 kg bauxite, 1 kg manganese powder and 1 kg dolomite are evenly mixed to obtain a mixed material; the mixed material is ground into powder by a vibration mill, and passed through a 400-mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45 to 0.9 mm, and the moisture content of the spherical particles is 11.5% to 17.5%; then the spherical particles are placed in a constant temperature box and dried at 110° C. for 2 hours to obtain a semi-finished product;

[0127] The rest is the same as in Example 1.

[0128] Comparative Example 3

[0129] The difference between this comparative example and Example 1 is:

[0130] S1: After slag, fly ash, soft clay, bauxite, manganese powder and magnesia are pulverized respectively, 5 kg slag, 5 kg fly ash, 1 kg soft clay, 30 kg bauxite, 1 kg manganese powder and 1 kg magnesia are evenly mixed to obtain a mixed material; the mixed material is ground into powder by a vibration mill and passed through a 400-mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45 to 0.9 mm, and the moisture content of the spherical particles is 11.5% to 17.5%; the spherical particles are then placed in a constant temperature box and dried at 110° C. for 2 hours to obtain a semi-finished product;

[0131] The rest is the same as in Example 1.

[0132] Comparative Example 4

[0133] The difference between this comparative example and Example 1 is:

[0134] S1: After ash, fly ash, soft clay, bauxite and manganese powder are crushed respectively, 5 kg ash, 5 kg fly ash, 1 kg soft clay, 30 kg bauxite and 1 kg manganese powder are evenly mixed to obtain a mixed material; the mixed material is ground with a vibration mill and passed through a 400-mesh sieve to obtain a fine powder of the mixed material; the fine powder of the mixed material is added to a disc granulator for granulation in multiple times, and atomized water vapor is applied during granulation to prepare spherical particles with a particle size of 0.45 to 0.9 mm, and the moisture content of the spherical particles is 11.5% to 17.5%; then the spherical particles are placed in a constant temperature box and dried for 2 hours at 110°C to obtain a semi-finished product; performance test

[0135] The performance indicators of the ceramsite fracturing proppants in Examples 1 to 14 and Comparative Examples 1 to 4 were tested according to Q / SY 17125-2019 “Performance Indicators and Evaluation Test Methods of Fracturing Propants”, and the data results are shown in Table 1.

[0136] Table 1 Performance indicators of ceramsite fracturing proppants in Examples 1 to 14 and Comparative Examples 1 to 4

[0137]

[0138]

[0139] The present invention uses ash and bauxite as main raw materials, and mixes a certain amount of fly ash, and improves the compressive strength and density of the fracturable proppant by utilizing the porous structure and wear resistance of the ash and the filling performance of the fly ash, thereby improving the anti-crushing ability of the proppant. By analyzing the test data of Examples 1 to 4, it can be seen that the addition amount of ash and fly ash cannot be too much. Although ash and fly ash can reduce the bulk density and apparent density of the proppant, they will also cause the crushing rate to increase. Therefore, it is necessary to optimize their addition amount.

[0140] By analyzing the test data of Example 1 and Comparative Examples 1 to 4, it can be seen that, firstly, the bulk density, apparent density and crushing rate of the ceramsite fracturing proppant prepared by using ash and fly ash to mix bauxite are lower than that of using only fly ash to mix bauxite, which is mainly due to the strong and durable compressive and abrasion resistance of the ash. Secondly, since dolomite and magnesia can promote the speed of solid phase reaction and accelerate the filling of voids, the densification degree of the sample is improved, and the compressive strength and crushing resistance of the proppant are improved.

[0141] By analyzing the test data of Examples 5 to 14, it can be seen that by further introducing silicate modifiers, sintering aids, coal tar and auxiliary agents, the sintering efficiency and thermal stability of the raw materials are promoted, the lattice deformation and thermal expansion are reduced, thereby reducing the risk of deformation and cracking of the proppant, enhancing the mechanical properties and density of the proppant, and further improving the anti-crushing ability.

Claims

1. A ceramsite fracturing proppant prepared using power plant ash, characterized in that: The ceramsite fracturing proppant is made of the following raw materials in parts by weight: 5 to 35 parts by weight of ash, 5 to 15 parts by weight of fly ash, 1 to 5 parts by weight of soft clay, 30 to 55 parts by weight of bauxite, 1 to 5 parts by weight of manganese powder, 1 to 3 parts by weight of dolomite, and 1 to 3 parts by weight of magnesia; The bauxite is high-iron bauxite, and the content of Fe2O3 in the high-iron bauxite is 22% to 25%; The bauxite includes high-grade bauxite and low-grade bauxite, and the mass ratio of the high-grade bauxite to the low-grade bauxite is 2-3:4-5.

2. The ceramsite fracturing proppant prepared using power plant ash according to claim 1, characterized in that: The raw materials further include 2 to 4 parts by weight of a modifier, wherein the modifier is a silicate, and the silicate is at least one of zinc silicate and barium silicate.

3. The ceramsite fracturing proppant prepared from power plant ash according to claim 2, characterized in that: The raw material also includes 2 to 4 parts by weight of a sintering aid, and the sintering aid is at least one of non-metallic boride, Cr2O3, and ZrO2.

4. The ceramsite fracturing proppant prepared from power plant ash according to claim 3, characterized in that: The non-metallic boride is any one of boric acid and boron nitride.

5. The ceramsite fracturing proppant prepared using power plant ash according to claim 4, characterized in that: The raw materials also include 1 to 3 parts by weight of coal tar.

6. The ceramsite fracturing proppant prepared from power plant ash according to claim 5, characterized in that: The raw material further includes 1 to 3 parts by weight of an auxiliary agent, wherein the auxiliary agent is at least one of magnesium chloride and aluminum dihydrogen phosphate.

7. A method for preparing ceramsite fracturing proppant prepared by using power plant ash according to any one of claims 1 to 6, characterized in that: The steps include: S1: After weighing and crushing the raw materials, mixing, grinding, sieving, spray granulating and drying to obtain a semi-finished product; S2: Sintering the semi-finished product in stages, heating from 100-120°C to 750-850°C for 1-2h, heating from 750-850°C to 1120-1150°C for 1.5-2.5h, then keeping the temperature at 1120-1150°C for 20-60min, cooling and screening to obtain ceramsite fracturing proppant.